Learning through drama in the primary years - Farmer, David, ....-; Hurtado, David, ....- (S.l. : Dramaresource, 2011)
This practical handbook explores how to use the greatest resource that teachers have available to them – children's imagination. Play is a natural part of children's lives before they start school, helping them to make sense of their place in the world. Such creativity can be harnessed through drama to enable active and interactive learning experiences throughout the primary years and across the curriculum. The book includes 36 drama strategies along with over 250 cross-curricular activities and three extended lesson plans. Any teacher will be able to pick up this book, walk into a classroom and deliver exciting active learning methods in virtually any subject area.
Keywords: Dramatische expressie -- Basisonderwijs